2017
DOI: 10.18632/oncotarget.16156
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 overexpression enhances progression and chemoresistance of urothelial carcinoma

Abstract: Abnormal activation of Notch signaling is involved in the etiology of various diseases, including cancer, but the association between Notch3 expression in urothelial cancer and clinical outcome remains unclear, and the molecular mechanisms underlying Notch3 signaling activation are not well defined. In this study we examined 59 urothelial cancer patients and found that Notch3 was more highly expressed in human urothelial cancer tissues than in non-tumorous bladder tissue samples, with Notch3 overexpression bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…We found that NR2F6 is also overexpressed in cervical squamous cell carcinoma, stomach adenocarcinoma, uterine corpus endometrial carcinoma, bladder urothelial carcinoma and breast invasive carcinoma tissue. Moreover, previous studies also indicated that Notch3 signaling is activated in these tumor types . These findings suggest that the NR2F6/Notch3 axis might also be relevant in tumor types in addition to EOC, and plays an important role in tumor progression.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…We found that NR2F6 is also overexpressed in cervical squamous cell carcinoma, stomach adenocarcinoma, uterine corpus endometrial carcinoma, bladder urothelial carcinoma and breast invasive carcinoma tissue. Moreover, previous studies also indicated that Notch3 signaling is activated in these tumor types . These findings suggest that the NR2F6/Notch3 axis might also be relevant in tumor types in addition to EOC, and plays an important role in tumor progression.…”
Section: Discussionmentioning
confidence: 53%
“…The high rates and patterns of therapeutic failure seen in EOC patients are consistent with a steady accumulation of drug‐resistant CSCs . Previous reports demonstrated that the Notch3 signaling pathway is critical for the regulation of CSCs and facilitating tumor resistance to platinum . Therefore, targeting Notch3 signaling appears to be a rational and innovative approach for the treatment of EOC.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Notch3 was shown to contribute to drug resistance when Notch3 knockdown combined with cisplatin chemotherapy eradicated drug‐resistant urothelial cancer cell clones. Notch3 knockdown also reduced bladder cancer progression in vivo, an observation perhaps most suggestive that Notch3 could be a suitable chemotherapeutic target for treating urothelial cancer .
Notch3 expression was found to be positively correlated with the Gleason score, and high expression of Notch3 was seen in prostate cancers with high metastatic potential.
…”
Section: Urogenital Cancersmentioning
confidence: 85%